AVALIAÇÃO DE CAPIM MULATO II COM DIFERENTES ADITIVOS SEQUESTRANTES - ROLON, João Gleidson Nunes; AMARAL, Pedro Nelson Cesar do; CARPEJANI, Graziela Cáceres; HONORATO, Paola Kerolaine dos Santos; CANDIDO, Anderson Ramires; COSTA, Genilson Fernando da (ANAIS DO ENIC, 2018)
-